Mga Bayaning Walang Kapa: Struggles and Coping of Ivatan Primary Caregivers of Children with Special Needs in the Province of Batanes - William Jo Se Billote; Kyle Ponce; Leonard Taghap; Samantha Jaslyn Nicole Arca; Christine Mae Villa (Philippine Association of Institutions for Research, Inc., 2021)
Primary caregivers of children with special needs encounter a host of new challenges and face reality and shock of diagnosing the disability itself. This study employed a descriptive research method to identify and describe the struggles of 18 Ivatan primary caregivers and their coping strategies in terms of gender in the Province of Batanes. Inventory questionnaires were used to gather data. Using Mean Analysis and ANOVA One-Way Repeated Measures, the Ivatan primary caregivers' prevalent struggles are Financial, Health, Social, Family, and Emotional. In terms of gender, both males and females experienced all the areas of struggle. Ivatan primary caregivers' struggles experienced, the more prevalent coping strategies used by Ivatan primary caregivers are Problem Solving, Cognitive Restructuring, and Social Support. Male and female primary caregivers used all the coping strategies except Social Withdrawal and Self-Criticism. Males utilized problem-solving the more while females utilized Cognitive Restructuring. Despite the various struggles that the Ivatan primary caregivers experienced, they find ways to cope with them.